Evaluations of healing potential of ethanol extract from Macrothelypteris torresiana (Gaudich) aerial parts - Sumanta Mondal; Harshavardhan K Reddy; Pakalapati R Vidya; Debjit Ghosh; Sundararajan Raja (International Journal of Phytomedicine, 2015)
The aim of the present study is to evaluate healing potential of 5% and 10% (w/w) ethanol extract from Macrothelypteris torresiana aerial parts (EEMTAP) in simple ointment (family thelypteridaceae). In excision wound model the ethanol extract from M. torresiana aerial parts showed significant increase in percentage wound closure and increased rate of epithelization. In incision wound model, EEMTAP treated animals showed increase in breaking strength when compared with control group. Similarly, the efficacy of treatment of chemical and thermal burn injuries in rats showed significant reduction in the burn wound area when compared with control group animals. These results showed that the burn wounds of untreated groups were contaminated, as they were not repaired, while those of treated groups by silver sulfadiazine and EEMTAP restored the normal architecture more rapidly and the percentage wound closure time was significantly reduced. In dead space wound model the ethanol extract treated animals (200 mg/kg, p.o.) showed significant increase in both wet and dry weight of granulation tissue. Estimation of hydroxyproline content in the granulation tissue revealed that the animal groups treated with EEMTAP had high hydroxyproline content as against the control group. The histological studies of the wound tissues revealed that the granulation tissue of the control group of animals showed more aggregation of macrophages with few collagen fibers, persistent inflammation, oedema and with chronic inflammation. In the case of povidone iodine treated animal possess significant increase in collagen deposition showing lesser macrophages with granulation tissue formation and lesser fibroblasts. In the case of 5% (w/w) EEMTAP treated animals revealed that moderate collagen deposition, macrophages and fibroblasts were noticed and the wounds treated with 10% (w/w) EEMTAP in simple ointment showing significant increased collagenation, few macrophages and capillaries.